PEMETAAN KONDISI KARANG TEPI (FRINGGING REEF) DAN KUALITAS AIR PANTAI ANGSANA KALIMANTAN SELATAN - Yunandar, Yunandar (Bumi Lestari; Vol 11 No 1 (2011), 2011)
This research aimed to: (a) identified and delineated coverage coral reef area on coastal Angsana based on  value  spectral;  (b)  coral  reef  area’s  calculated;  (c)  coral  reef  area’s  mapping  conditions  and  (d) Estimated of water quality on coastal study area based on field algorithm model. Methods employed in this research was combined field survey, remote sensing and water quality. The result obtained Aster band 321 discovered three of class habitat coral with coverage life coral in middle, sands and rubble mixed on fringing reef and seagrass not found. Life coral discovered on station 1 (6 hectare) and Aster (5 hectare), based on component of population most coral dead dominated on station 1 (3,5 hectare) and (2,5 hectare), minority of larges on station 5 (1,5 hectare survey; 0,5 hectare Aster). Coral with fair conditions on station 2,3,5 with percent coverage 43,59%; 26,45%; 25,2%, poor on station 4 (22,06%) and 6 (12,0%), the best category  on  station  1  (69,6%).  Statistic  model  discovered  for  salinity  ( 0/00 )  =  18,780  -  560,659  (B6 (B4+B5)).
Keywords: mapping; coral reefs; water algorithm; water quality